Development and Adjustment of an Algorithm for Identifying Drug-Related Hospital Admissions in Pediatrics - Schulze, Christopher; Toni, Irmgard; Moritz, Katrin; Eberl, Sonja; Rascher, Wolfgang; Neubert, Antje (Journal of Patient Safety, 2022)
Objective Adverse drug events (ADEs) in the outpatient pediatric pharmacotherapy can be serious and lead to inpatient admissions. Recent research only focused on ADE identification during hospitalization. The aim of the present study was to develop an algorithm to identify drug-related hospital admissions in pediatrics. Methods A systematic literature research was performed, and a pediatric trigger tool for identifying drug-related inpatient admissions was built. The initial version was tested in a sample of 292 patients admitted to a German university children's hospital. Subsequently, the tool was further improved by combining different modules as a novel approach. Results The obtained algorithm with 39 triggers in 5 modules identified drug-related inpatient admissions at a sensitivity of 95.5% (95% confidence interval [CI], 89.3%-100%) and a specificity of 16.5% (95% CI, 11.9%-21.2%), respectively. After modifications including trigger activation requiring a combination of different modules, specificity increased to 56.9% (95% CI, 50.7%-63.0%). Identifying 36 of 44 ADEs leading to admission, sensitivity remained high (81.8% [95% CI, 70.4%-93.2%]). The overall positive predictive value was 25.2% (95% CI, 18.1%-32.3%). Conclusions The algorithm is the first trigger tool to identify ambulant acquired ADEs leading to hospital admission in pediatrics. However, the underlying patient sample is small. Using a larger population for refinement will allow further specifications and reduction in the total amount of triggers and thus signals.
CRIS-Team WoS Importer:2022-08-26

Fever: physiology, pathophysiology, clinical signs and treatment Fieber: Physiologie, Pathophysiologie, klinische Zeichen und Therapie - Marek, I.; Moritz, Katrin; Rascher, Wolfgang; Neubert, Antje (Monatsschrift Kinderheilkunde, 2021)
Background: Fever is a common leading symptom in children presenting in emergency departments and clinical practices. Parents are often uncertain how to treat the febrile child. Objective: This article presents the current knowledge regarding the physiology and pathophysiology of fever in children and the latest evidence on which the recommendations for pharmacotherapy is based. Material and methods: A structured search and analysis of the literature was performed. Results and discussion: Under physiological conditions the temperature regulation center in the hypothalamus controls a stable core body temperature of 37 °C by balancing heat production and loss. Fever develops when mediators of inflammation override the inhibition of excessive heat production mediated by warmth-sensitive neurons in the hypothalamus. Prior to symptomatic treatment of pediatric fever the clinical cause of the fever has to be found and if necessary a causal treatment has to be initiated. This is especially true for high-risk patients, such as neonates, immunosuppressed individuals and children with foreign bodies, such as catheters. In terms of pharmacotherapy two well-established drugs (paracetamol and ibuprofen) are available for the symptomatic treatment of fever. Monotherapy should be preferred over combined or alternating drug administration. Ibuprofen is slightly superior compared to paracetamol with both drugs showing similar safety profiles. There is insufficient evidence to justify the prophylactic use of antipyretics to prevent febrile seizures.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Child; Evidence-based medicine; Febrile seizure; Pharmacotherapy; Thermoregulation

Oral Presentation: Drug-Related Hospital Admissions in Paediatrics-Is There Potential for Prevention? - Toni, Irmgard; Ahne, G.; Marek, Ines; Moritz, Katrin; Schulze, Christopher; Schreeck, F.; Makosi, D. M.; Rascher, Wolfgang; Neubert, Antje (DRUG SAFETY, 2022)
CRIS-Team WoS Importer:2022-10-07

Zulassungseinschränkung der Antihistaminika der ersten Generation für Kinder unter 3 Jahren aufgrund eines negativen Nutzen-Risiko-Verhältnisses - Moritz, Katrin; Rascher, Wolfgang; Toni, Irmgard; Zahn, Julia; Neubert, Antje (Monatsschrift Kinderheilkunde, 2020)
First generation H1 antihistamines (e.g. dimenhydrinate, diphenhydramine and doxylamine) have been an essential component in pediatric drug treatment for many years. In recent years there have been an increasing number of reports of serious (including fatalities) side effects in infants following the use of these drugs. For this reason, in 2017 the Federal Institute for Drugs and Medical Devices (BfArM) initiated a risk assessment procedure and reassessed the benefit-risk ratio based on the available data. As a result the oral and rectal use of antiemetics containing dimenhydrinate and diphenhydramine in children below 3 years of age suffering from nausea and vomiting associated with simple gastroenteritis and feverish infections are no longer indicated. In addition, doxylamine became a prescription-only drug. This article illustrates the background to why and how the use of first generation H1 antihistamines is now restricted and the effects which the reporting of adverse drug reactions can have.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Adverse drug reaction; Dimenhydrinate; Histamine H1 antagonist; Pediatrics; Pharmacovigilance